2020
DOI: 10.3390/microorganisms8081131
|View full text |Cite
|
Sign up to set email alerts
|

The ComX Quorum Sensing Peptide of Bacillus subtilis Affects Biofilm Formation Negatively and Sporulation Positively

Abstract: Quorum sensing (QS) is often required for the formation of bacterial biofilms and is a popular target of biofilm control strategies. Previous studies implicate the ComQXPA quorum sensing system of Bacillus subtilis as a promoter of biofilm formation. Here, we report that ComX signaling peptide deficient mutants form thicker and more robust pellicle biofilms that contain chains of cells. We confirm that ComX positively affects the transcriptional activity of the PepsA promoter, which controls the synthesis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 87 publications
3
33
0
Order By: Relevance
“…Among many other functions, it has been shown that inactivation of QS can lead to a delay in sporulation entry 36 , which is in accordance with our observation of a reduced sporulation level observed in post-ST variants (Fig.1b). Interestingly, it has been discussed that ComQXPA system may act as a switch that contributes to the stochastic initiation of sporulation which, consequently, is able to achieve a bet-hedging behavior to limit the investment in population growth, and favor commitment to late growth adaptive processes 36 .…”
Section: Post-st Variants Show Loss-of-function Mutations In Qs Genessupporting
confidence: 92%
See 1 more Smart Citation
“…Among many other functions, it has been shown that inactivation of QS can lead to a delay in sporulation entry 36 , which is in accordance with our observation of a reduced sporulation level observed in post-ST variants (Fig.1b). Interestingly, it has been discussed that ComQXPA system may act as a switch that contributes to the stochastic initiation of sporulation which, consequently, is able to achieve a bet-hedging behavior to limit the investment in population growth, and favor commitment to late growth adaptive processes 36 .…”
Section: Post-st Variants Show Loss-of-function Mutations In Qs Genessupporting
confidence: 92%
“…Thus, the enhanced biofilm formation displayed by post-ST variants resulted at first contradictory. However, it has been recently described that B. subtilis strains carrying mutations in genes of the ComQXPA QS system actually form pellicles with more matrix components than the wild-type strain 36 . In fact, ComQXPA mutants are able to develop earlier and thicker biofilms even though with decreased surfactin production.…”
Section: Post-st Variants Show Loss-of-function Mutations In Qs Genesmentioning
confidence: 99%
“…Importantly, matrix gene expression in the nascent pellicle is temporally and spatially heterogeneous, after a highly heterogeneous matrix production during initiation of the pellicle, the majority of cells express the genes for matrix production in the middle of biofilm development (around 24 hours) (12). In the later stages, the population becomes heterogeneous again, only a fraction of the cells will produce the matrix (12), while spores also appear (13,14). Such temporal heterogeneity is mirrored by physical heterogeneity; during the initial and later stages of pellicle development, next to a robust, highly matrix-expressing population, a fragile fraction is also present, within which the cell-cell aggregation can be easily disrupted (12).…”
mentioning
confidence: 99%
“…A loss of antagonisms and the concomitant increase in the production of secondary metabolites that are beneficial to plants (IAA, acetoin, lipopeptides) in coculture (SQR9△spo0A+FZB42) may in part explain the beneficial effect on plants. It has been reported that the amphipathic lipopeptide surfactin acts a 'public good' produced by B. subtilis and that it is necessary for multicellular swarming by reducing the water surface tension (16). In this study, this function may be supplemented by the lipopeptides bacillomycin D and fengycin, which can also act as biosurfactants and could be therefore potential 'public goods' in coculture environments (34).…”
Section: Discussionmentioning
confidence: 84%
“…The production of public goods by Bacillus, such as extracellular matrix (EPS), siderophores and lipopeptide (e.g. surfactin), are controlled by a quorum sensing system (15,16) and by global transcriptional regulators such as Spo0A and DegU (14,17). Social interactions among Bacillus strains influence the production of public goods at the community level; however, to the best of our knowledge, few studies have focused on how antagonisms or cooperativity affect secretions of lipopeptide antibiotics and plant growth promoting hormones by bacteria in multicellular groups.…”
Section: Introductionmentioning
confidence: 99%